Preparation and Evaluation of Amorphous Solid Dispersion of Etoricoxib, Employing A Fast Approach for Polymer Selection - Shaikh, Bandenawaz M.; Gajbe, Jitendra W.; Madgulkar, Ashwini R.; Bhalekar, Mangesh R.; Shinde, Minakshi B. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2025)
BackgroundNonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to manage pain and inflammation but are associated with gastrointestinal and cardiovascular risks, especially with COX-2 inhibitors. Topical delivery systems offer a safer alternative by minimizing systemic exposure; however, poor solubility and limited skin penetration remain challenges. Enhancing solubility through solid dispersion and incorporating it into a gel formulation may improve permeability and therapeutic effectiveness, addressing the need for safer and more efficient topical NSAID delivery.IntroductionThis investigation aimed to enhance the solubility and dissolution rate of poorly water-soluble etoricoxib through the development of solid dispersions using the kneading method.MethodsA suitable carrier was selected from a pool of candidates based on polarised microscopy analysis. The influence of a solubilizer on amorphization was evaluated. Solid dispersions of Etoricoxib and its corresponding physical mixtures, incorporating or excluding the solubilizer, were prepared at varying drug-to-carrier ratios. Yield, drug content, saturation solubility, and in vitro dissolution profiles of these formulations were determined. Solid-state characterization using Fourier Transform-Infrared (FTIR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), and differential scanning calorimetry (DSC) techniques was conducted.ResultsFTIR spectra indicated the formation of intermolecular hydrogen bonds within the dispersions. XRD, SEM, and DSC analysis confirmed the amorphous transition of crystalline etoricoxib in all the prepared solid dispersions. In comparison to pure etoricoxib and its physical mixes, the produced solid dispersions showed significantly improved dissolution and solubility.DiscussionSolid dispersion technology effectively enhanced the solubility and dissolution of poorly water-soluble etoricoxib. Polarised microscopy also proved valuable for rapid excipient screening. However, the study was limited by the narrow range of solubilizers tested. While Poloxamer 407 was selected for its availability and untapped potential, broader screening of advanced solubilizers could offer improved outcomes.ConclusionThe solubility increased from 99.08 to 296.8 μg/ml and the dissolution rose from 69.32% to 98.07%. These findings suggest that the kneading method and Poloxamer successfully produced amorphous solid dispersions of etoricoxib with significantly enhanced solubility and dissolution properties, potentially improving its bioavailability.
Keywords: amorphization